God in One Person
IX, 204 p.
Keywords: This text defends a special focus on Jesus in theistic faith, whilst denying his divinity. Having limited the genuine choice in Christology to orthodoxy or unitarianism, it argues first for the prior improbability of an incarnation, examining and dismissing possible justifications.